2021
DOI: 10.1007/s11764-021-01100-z
|View full text |Cite|
|
Sign up to set email alerts
|

Sensory signs and symptoms in women with self-reported breast cancer–related lymphedema: a case–control study close up

Abstract: Purpose: It is not clear to what extent signs and symptoms other than arm swelling, including pain, altered sensory function and body perception disturbances, differ between women with measurable and non-measurable breast cancer-related lymphedema (BCRL). A case-control study was performed to compare these signs and symptoms between 1) women with self-reported BCRL with objectively measurable swelling; 2) women with self-reported BCRL without objective confirmation; and 3) a control group with no self-reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Individuals with BCRL report a wide range of symptoms, including swelling, heaviness or tightness, pain or discomfort, numbness or tingling sensations, reduced range of motion, skin changes (e.g., thickening or discoloration), and impaired function in performing daily activities in the affected limb. [9][10][11] These symptoms can vary in severity and may not be experienced by every individual with lymphedema. Early recognition and management of these symptoms are essential for minimizing their impact on quality of life and for preventing complications associated with the condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with BCRL report a wide range of symptoms, including swelling, heaviness or tightness, pain or discomfort, numbness or tingling sensations, reduced range of motion, skin changes (e.g., thickening or discoloration), and impaired function in performing daily activities in the affected limb. [9][10][11] These symptoms can vary in severity and may not be experienced by every individual with lymphedema. Early recognition and management of these symptoms are essential for minimizing their impact on quality of life and for preventing complications associated with the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Early recognition and management of these symptoms are essential for minimizing their impact on quality of life and for preventing complications associated with the condition. [8,12] The majority of current literature focuses primarily on identifying upper limb symptoms associated with BCRL, [10] and on identifying factors contributing to the development of BCRL, [13,14] , [9] leaving a gap in understanding the complex lymphedema symptomatology. To address this gap, latent class analysis (LCA) and network analysis offer promising approaches to identify distinct symptom patterns and symptom interrelationships within the BCRL population.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown both central sensitization patterns that produce changes in pain sensitivity stimulus [ 11 ] and rotator cuff damage in the shoulder and neck area in women who survived BC after post-mastectomy surgery [ 12 ]. BC-related lymphedema is a sensorimotor disabling sign that is accompanied by pain, upper extremity motor disorders [ 13 , 14 ], and skin alterations [ 15 ]; it appears in 14–54% of survivors (almost one in five BC survivors) after axillary surgery or irradiation [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%